Elaboración de compost utilizando cabello humano y aplicando dos fuentes de microorganismos: microorganismos eficientes (EMS) y trichoderma spp, como agentes aceleradores de compostaje - Jácome Sarchi, Guillermo Alexander (Tierra Infinita, 2015)
In order to avoid contamination of large areas because of poor garbage disposal was achieved leverage human hair is removed in beauty salons, as raw material for the production of compost also inoculated microorganisms to accelerate this process, compost is an organic fertilizer that is used as fertilizer edaphic, can contribute to the development of agriculture, and environmental conservation.The technological process began with the collection of the raw material, which was submitted to the composting process, by a space of 16 weeks, employment is a complete Design at random with 9 treatments and 3 replicates, each experimental unit was formed with 50kg of organic matter to composting, we used two doses of human hair: the 5 and 10 %, two different groups of microorganisms: efficient microorganisms (EM) and Trichoderma spp, in conjunction with manure and grass trimmed. It was found that the formulation of treatment T2 (2% efficient microorganisms + 10% + 24% Human Hair guinea pig manure. + 64% pruning grass) was the most suitable for obtaining an optimal concentration of macronutrients, secondary elements and micronutrients with values 0.12% nitrogen, 0.028% phosphorus, 0.60% potassium, 0.56% calcium, 0.085% sulfur, 0.059% magnesium, 6.01 ppm boron, 4.11 ppm copper, 127.13 ppm Iron, 56 ppm manganese and 22.29 ppm zinc.. In addition a slightly acid pH reached 6.27, an electrical conductivity of 12.91 mS / cm which results in a compost with a strong salt concentration, the yield was 65%, and the cost of production per kilogram of compost merited a value of $ 0.07.